Avaliação da toxicidade e genotoxicidade do extrato bruto das folhas da espécie Randia ferox (Cham & Schlecht) DC. - Pappis, Lauren (2015)
Around the world, the use of plants as means of medicinal source is an ancient costume. Mainly in developing countries, medicinal plants are the only choice of treatment. Besides, the population believes that by being natural products, medicinal plants are not a risk for health. However, several studies have proven that some plants used as medicine show toxicity levels that endanger human health. Of particular interest, the leaves of the popularly known as “limoeiro-do-mato’, the specie Randia ferox from the Ruceaceae family, are used as anti-inflammatory and healing. The aim of this study was to quantify the secondary metabolic in HPLC method and assess the acute and sub-acute toxicity of the crude extract of bothleaves (CEL) and genotoxicity for that plant. In HPLC method, it was possible to quantify quercetin (6,85 mg/g), chlorogenic acid (6,38 mg/g), rutin (5,52 mg/g), quercitrin (2,71 mg/g), luteolin (1,93 mg/g), and gallic acid (0,71 mg/g). In acute toxicity, rats Wistars of both genders was treated with CEL in a concentration of 2000 mg/Kg. The animals were observed during 14 days without any animal death nor observed change of behavior. In addition, their food intake, body weight gain, biochemical and hematological parameters did not show differences in comparison with the control group. According to OECD Guidelines 423, the specie was classified as five category, with lethal dose estimated between 2000-5000 mg/Kg. In the sub-acute study, the Wistars rats of both genders were treated during 28 days, separated in four groups, as follows: control group treated with water; and treatment groups where CEL was administrated in different concentrations (100, 200 and 400 mg/Kg). There was no significant difference of weight neither in the ingestion of food of the animals. The rat’s blood was biochemically and hematologicaly evaluated. Besides, all livers and kidneys were analyzed for toxicity and genotoxicity parameters. The both genders of 200 and 400 mg/Kg showed a decrease of TBARS, ROS and PC in the livers, which may imply an antioxidant capacity of CEL. The DNA CA increased in both genders at 400 mg/Kg in the livers, wich may suggest a genotoxicity capacity. In the kidneys of all female of the groups treated with CEL, an increase of ROS was observed. However, TBARS and other kidney’s damage markers did not show any difference from the control group. Such results suggest the absence of nephrotoxicity. A decrease of CHO occurred in the male rats treated with 200 and 400 mg/Kg, but the values laid within the reference dates, therefore such decrease was not due to a hepatotoxicity. In female treated with CEL in 200 and 400 mg/Kg, increase of GLU occurred. As the same did not happen with the males, those altered values suggest a hormone variation. The treatment sub-acute of CEL of Randia ferox showed a toxicity capacity only in the highest concentration.